The impact of a clinical decision support service on adherence to clinical guidelines and achieving target low-density lipoprotein cholesterol levels in patients at risk of cardiovascular events in the Kemerovo Oblast (SuccESS Study in the Kemerovo Oblast) - M. V. Ezhov; I. V. Sergienko; F. N. Paleev; A. M. Shangina; Y. E. Efremova; O. L. Barbarash; I. L. Strokolskaya; A. V. Alekseenko; K. S. Astrakova; I. L. Mikheenko; A. E. Uranov; A. A. Gartung; et al. (Российский кардиологический журнал)
Aim. To evaluate the effectiveness of an analytical service with a clinical decision support system (CDSS) in increasing the frequency of monitoring low-density lipoprotein cholesterol (LDL-C) levels in patients with acute cardiovascular events (CVE), coronary artery disease (CAD), or dyslipidemia in the Kemerovo Oblast.Material and methods. This non-interventional retrospective multicenter study was conducted in 16 health facilities of the Kemerovo Oblast from January 1, 2022 to March 31, 2024. There were main cohort (6694 patients with CVE) and an additional cohort (12174 patients with CAD or dyslipidemia). The study included two following follow-up periods: before (12 months) and after (15 months) the CDSS implementation. The CDSS was implemented through integration into the regional health information system (HIS). Physicians at the automated workplace in the single-window mode in the HIS received recommendations for the examination and treatment of patients according to clinical guidelines and Order 168n, as well as access to an analytical platform for monitoring patients with suboptimal indicators (including LDL-C ³1,4 mmol/L or no data on LDL-C at very high cardiovascular risk). The primary endpoint was the proportion of patients with a single determination of LDL-C levels within 6 and 12 months after the index event.Results. In the main cohort, the proportion of patients with LDL-C assessment increased from 11,1% to 14,8% (relative change +33%, p<0,001). In the additional cohort, the same indicator increased from 10,5% to 15,0% (relative change +43%, p<0,001). A significant improvement in the completeness of electronic health records with clinical parameters was noted. The proportion of patients not covered by outpatient monitoring decreased in the main cohort from 62,2% to 40,2% (for patients with stroke/transient ischemic attack) and from 41,6% to 28,9% (for patients with myocardial infarction/unstable angina). In the additional cohort, the proportion of patients without outpatient monitoring decreased from 50,6% to 38,9%. Achievement of the target LDL-C level in the additional cohort increased from 10,8% to 14,4% (relative change +34%).Conclusion. The implementation of the CDSS increases physicians' adherence to clinical guidelines and improves the quality of care for patients with cardiovascular diseases. An increase in the frequency of LDL-C monitoring, visits to specialists, and the intensity of lipid-lowering therapy was noted. The CDSS improves the continuity of care and the quality of outpatient monitoring, as well as identifies problem healthcare areas.